2019
DOI: 10.1016/j.ceramint.2019.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of submicronic and nanometric boron carbides obtained by Spark Plasma Sintering: Influence of B/C ratio and oxygen content

Abstract: Boron carbide samples exhibiting nanometric and submicronic microstructure were sintered by Spark Plasma Sintering to investigate the effect of grain size on mechanical properties. The mechanical properties of sintered monoliths were characterized at the grain and macroscopic scales. Although nanostructured material exhibits finer grains than the submicronic material (i.e. mean diameter of 82 vs. 474 nm), its apparent rigidity and hardness are found to be reduced by 6.8 % and 8.4 % respectively. This contradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…B/C < 4), they have highlighted that hardness and toughness also decreases due to the presence of free carbon as secondary phase located at grain boundaries. In addition, in previous works [12,13], we have shown that the presence of structural oxygen in boron carbide lattice, leading to a boron oxycarbide phase, induces a decrease in both hardness and elastic properties for oxygen content higher than 2 wt.%. Some studies have highlighted the benefit effect of impurities removing from starting powder on elasticity and hardness of boron carbide monoliths sintered by Spark Plasma Sintering (SPS), displayed in Table 1.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…B/C < 4), they have highlighted that hardness and toughness also decreases due to the presence of free carbon as secondary phase located at grain boundaries. In addition, in previous works [12,13], we have shown that the presence of structural oxygen in boron carbide lattice, leading to a boron oxycarbide phase, induces a decrease in both hardness and elastic properties for oxygen content higher than 2 wt.%. Some studies have highlighted the benefit effect of impurities removing from starting powder on elasticity and hardness of boron carbide monoliths sintered by Spark Plasma Sintering (SPS), displayed in Table 1.…”
Section: Introductionmentioning
confidence: 58%
“…According to literature, the mechanical properties of full dense monoliths depend on variation of chemical composition, i.e. carbide stoichiometry and presence of secondary phases such as free carbon [11][12][13]. Niihara et al [11] emphasized that, for a B/C ratio higher than 4, increasing B content in boron carbide plates obtained by chemical vapor deposition resulted in reduction of hardness and toughness, which was attributed to reduction of bond strength in the boron carbide structure.…”
Section: Introductionmentioning
confidence: 99%
“…The powder sintering was carried out from a commercial (H.C. Starck) submicrometric powder HD 20 of boron carbide with a purity of 99.5%, an average diameter of 400 nm and a specific area of 24 m 2 •g − 1 [22][23] . Powder has been densified without sintering additives using SPS facility (Fuji-Syntex, Dr Sinter 825, Japan) under dynamic vacuum.…”
Section: Boron Carbide Sample Preparationmentioning
confidence: 99%
“…Boron carbide is a covalent material characterized by a high melting point, relatively low density, and high chemical resistance; when in the form of dense polycrystals, it is characterized by a high Young modulus, extreme hardness, and good mechanical properties [1][2][3]. Such properties are suitable for boron carbide applications in components resistant to abrasion in ball mills, nozzles, parts of machinery, and equipment and as parts of antiballistic armor.…”
Section: Introductionmentioning
confidence: 99%